2018
DOI: 10.1021/acs.langmuir.8b01065
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Organic Gels of Catechol-Based Ligands with Ni(II) Acetate for Dye Adsorption

Abstract: Metal organic gels (MOGs) are a class of supramolecular complexes, which have attracted widespread interest because of the coupled advantages of inorganic and organic building blocks. A new compound terminated with catechol was synthesized. This new compound can be used to coordinate with Ni to form MOGs. These MOGs show favorable viscoelasticity and wormhole-shaped porous structures, which were confirmed by transmission electron microscope and scanning electronic microscope images. Taking the benefits of poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Zhao et al [10] synthesized a magnetic metal-organic framework for removal of 245 mg g À 1 MB from aqueous phase. Yue Hong et al [11] prepared a metal-organic gels (MOGs), which showed porous structures and was used for adsorption of both anionic and cationic dyes. Wang et al [12] found a rGO (reduced graphene oxide), and Graphene-like structure of Boron nitridebased materials, which has a good effect on the adsorption of water pollutants through its hydrogen bonding and π-π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [10] synthesized a magnetic metal-organic framework for removal of 245 mg g À 1 MB from aqueous phase. Yue Hong et al [11] prepared a metal-organic gels (MOGs), which showed porous structures and was used for adsorption of both anionic and cationic dyes. Wang et al [12] found a rGO (reduced graphene oxide), and Graphene-like structure of Boron nitridebased materials, which has a good effect on the adsorption of water pollutants through its hydrogen bonding and π-π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, dye removal by adsorption is advantageous due to its relatively simple adsorption mechanism, removal efficiency, economic feasibility, and flexibility in the process involved. Persistent scientific efforts have been devoted to increasing the dye removal efficiency using various adsorbents based on polymers, gels, , thin films, nanocomposites, ,, clays, etc. Given a myriad of adsorbents, selecting an effective adsorbent is quite challenging as concerns regarding their reusability, adsorption capacities, amount of adsorbent required, and dye removal rates are to be quizzed.…”
Section: Introductionmentioning
confidence: 99%
“…Gel-based adsorption thus will have promising applications in dye removal from wastewater for the reasons mentioned above. These adsorbents can remove both anionic and cationic dyes , or can be specific to one particular ion. Most of the gel adsorbents investigated are based on hydrogels; , there are also a few reports where microgels, ionic liquid gels, , metallogels, , aerogels, etc., are tested for dye adsorption. Of late, there has been a growing interest in the preparation of organogels, which are polymeric networks swollen in an organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been developed and employed, such as various chemical methods including electrochemical processes (de Moura et al 2016;He et al 2016), advanced oxidation processes (Gayathri et al 2017;Alcocer et al 2018), and various physical treatment methods including coagulation/flocculation (de Camargo Lima Beluci et al 2019;Song et al 2019), membrane filtration (Han et al 2017;Zhu et al 2017), adsorption (Hadi et al 2016;Li et al 2017;Hong et al 2018;Li et al 2020) and biological treatment methods (Hosseini Koupaie et al 2013). Among these technologies, the adsorption is a promising technique due to the advantages of low cost, no secondary pollution, environmental friendliness, less energy consumption and excellent performance (Ahmed et al 2019;Hu et al 2019).…”
Section: Introductionmentioning
confidence: 99%